The Adoption of Digital Wallets and Their Influence on the Shopping Behavior of Urban Communities - R. Suprono Wahyujatmiko; Heru Kuncorowati; Chinthia Sari Yusriana (PT. Anagata Sembagi Education, 2026)
The rapid development of financial technology has led to significant changes in urban payment systems, particularly through the adoption of digital wallets. This transformation in payment methods has the potential to influence consumer shopping behavior beyond transactional efficiency, affecting consumption patterns and tendencies. This study aims to analyze the influence of digital wallet adoption on the shopping behavior of urban communities. A quantitative approach with an explanatory design was employed using a survey method. Data were collected from urban residents who actively use digital wallets and analyzed using linear regression. The results indicate that digital wallet adoption has a positive and significant effect on shopping behavior among urban consumers. The coefficient of determination reveals that digital wallet adoption explains a substantial proportion of the variance in shopping behavior. These findings suggest that the convenience and efficiency of digital payments play an important role in shaping consumption patterns in urban settings. This study contributes empirically to the literature on digital economy and consumer behavior by highlighting digital payment systems as a key determinant of urban shopping behavior.